To solve for x, we can start by simplifying both sides of the equation.
Starting with the left side: 13x + 26
And the right side: 3x - 34
Now we have the equation: 13x + 26 = 3x - 34
To isolate the variable x, let's get rid of the constant terms on both sides by subtracting 26 from both sides:
13x + 26 - 26 = 3x - 34 - 26
This simplifies to: 13x = 3x - 60
Next, let's isolate the x term on one side by subtracting 3x from both sides:
13x - 3x = 3x - 60 - 3x
This simplifies to: 10x = -60
Finally, isolate x by dividing both sides by 10:
10x/10 = -60/10
This simplifies to: x = -6
Therefore, the correct answer is x = -6.
Solve for x: 13x + 26 = 3x - 34.
Choose the correct answer:
x = -6
x = 3
x = -9
x = 18
1 answer